Porous ceramics of sodium potassium niobate system - D.V. Mamaev; O.V. Malyshkina; A.I. Ivanova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In our work, we used the finely dispersed polystyrene to produce porous samples of the piezoelectric ceramics. Samples of the sodium potassium niobate ceramics with pore concentrations of the 10, 20, 25, 30 and 40 volume percent were produced. The structure was analyzed and the temperature and frequency dependences of the dielectric constant of the obtained samples were investigated. It has been established that the presence of polystyrene in the process of sintering piezoceramic samples plays the role of a binder, which evaporates during high-temperature processing. At the same time, the binder contributes to stabilization of the dielectric properties of the ceramics. In the porous samples, there are no fluctuations of the permittivity in the low-frequency region, and the frequency range in which the permittivity values are independent of the frequency increases. It was found that already 34 volume percent of the pores worsen the mechanical strength of the sample. It is shown that the use of a simple problem of percolation theory does not allow assessing the mechanical strength of porous samples depending on the pore concentration.